PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBASIS PERMAINAN TRADISIONAL MARTUMBA TERHADAP HASIL BELAJAR PSIKOMOTORIK SENI TARI SISWA KELAS V UPT SD NEGERI 019 LUMBAN PURBA - Purba, Novi Kristina; Putra Afriadi; Try Wahyu Purnomo; Laurensia Masri Parangin Angin; Fajar Sidik siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Student Teams Achievement Division (STAD) cooperative learning model based on the traditional game Martumba on the psychomotor learning outcomes in dance arts of fifth-grade students at UPT SD Negeri 019 Lumban Purba. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of 38 students, including 19 students in the experimental class and 19 students in the control class. Data were collected using observation techniques through psychomotor assessment sheets. The results showed that the average pretest and posttest scores in the experimental class increased from 61.84 to 85.90, while in the control class they increased from 59.40 to 77.07. The hypothesis testing using the t-test indicated that t_count > t_table (5.56 > 2.02), meaning that Hₐ was accepted. Therefore, the STAD cooperative learning model based on the traditional game Martumba has a significant effect on students' psychomotor learning outcomes in dance arts.